ACCOUNTING UNDER CONDITIONS OF CHANGING PRICES FROM THE DEBT-OR AND CREDITOR VIEWPOINT. - Zieha, Eugene L. (The Accounting Review, 1953)
The article discusses different problems introduced into accounting by the tendency of the monetary unit to undergo almost constant changes in meaning. There are many aspects of the overall problem that, although they are frequently neglected in the current discussions of accounting under conditions of changing prices, appear worthy of additional attention. In many cases these deal with basic ideas that are often ignored by the critics of current methods in their attempts to reach a quick solution to outward manifestations of the problem. One of these fundamental, but neglected, ideas is that pertaining to the accountants' responsibilities towards debtors and creditors. Inherent in the discussions of the price level problem, but seldom approached directly, is the question of the relative position of the various types of equity holders. Yet any consideration of accounting procedure must give attention to the effect of the method followed upon the claims of those who supply the capital used in business operations.